Management and Surveillance of Frontal Sinus Violation following Craniotomy - Farag, Alexander; Rosen, Marc R.; Ziegler, Natalie; Rimmer, Ryan A.; Evans, James J.; Farrell, Christopher J.; Nyquist, Gurston G. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives In the setting of craniotomy, complications after traversing the frontal sinus can lead to mucocele formation and frontal sinusitis. We review the etiology of frontal sinus violation, timeline to mucocele development, intraoperative management of the violated sinus, and treatment of frontal mucoceles.Design Case series in conjunction with a literature review.Participants A total of 35 patients were included in this meta-analysis. Nine of these patients were treated at a tertiary academic medical center between 2005 and 2014. The remaining patients were identified through a literature review for which 2,763 articles were identified, of which 4 articles met inclusion criteria.Main Outcomes Measures Etiology of frontal violation, timeline to mucocele development, and method of management.Results The overall interval from initial frontal sinus violation until mucocele identification was 14.5 years, with a range of 3 months to 36 years. The most common cause of mucocele formation was obstruction of the frontal recess with incomplete removal of the frontal sinus mucosa. The majority of patients were successfully managed with an endoscopic endonasal approach.Conclusions Violation of the frontal sinus during craniotomy can result in mucocele formation as an early or late sequela. Image guidance may help avoid unnecessary frontal sinus violation. Mucoceles may develop decades after the initial frontal sinus violation, and long-term follow-up with imaging is recommended. While the endoscopic endonasal approach is usually the preferred method to treat these lesions, it may be necessary to perform obliteration or cranialization in unique situations.
Keywords: frontal sinusitis; craniotomy; mucocele; frontal sinus mucocele; craniotomy complications